The Australian program to develop the future national team and club development - Sweetenham, B. (2001)
B. Sweetenham presents on September 8, 2001 his ideas concerning the Australian program to develop the future national team and club development and he develops plans for Great Britain`s swimming program. Key points are: I. Australian National Youth Coach works with the best 18 and younger talent A. Working to have better prepared athletes moving into the National Team. B. Make sure the next group of athletes don`t have the same weaknesses of the current seniors. C. State Camps and Event Camps. D. It is the job of the National Youth Coach to make the transition from age group swimming to youth swimming to national swimming as difficult as possible. E. Visit the home programs and help them with their problems F. Swimmers moving onto the National Team should be better prepared than the previous group of swimmers was. G. 250 days on the road, away from home. H. It is always a challenge to innovate coaching. I. Sponsorships. J. Lactate Removal Set. K. Males and females should train separately. L. Challenge the coaches and evaluate the programs based on : 1. Top 3% of the swimmers in prelims 2. Top 2% of the swimmers in semifinals 3. Top 1% of the swimmers in finals 4. Top 1 % of the swimmers on relays M. Meet participation should be based on the 3, 2, 1 philosophy. 1. 3 meets at the swimmer`s level of proficiency. 2. 2 meets below the swimmer`s standards. a) Pressure to do things RIGHT. b) Practice WINNING. c) Be very critical of the swimmer at these meets. 3. 1 meet above the swimmer`s ability. a) Swim in higher age group. b) Swim in off events. c) Do only 1 event. d) Praise the swimmer at these meets. N. Look for 3% improvement a year. O. The Australian National Youth Coach works with the more talented and the more remote clubs. Britain must find more junior swimmers and be better prepared for National level swimming.